Togo 2020: Domestic politics, foreign affairs, socio-economic development - Dirk Kohnert (Africa Yearbook Volume 17: Politics, Economy and Society South of the Sahara in 2020, 2021)
Controversial constitutional and institutional reforms voted in May 2019 in parliament opened the way for President Gnassingbé to stand for a fourth and fifth term because the law does not apply retroactively. In February 2020, the President won again the disputed presidential elections and thus consolidated his power, assisted by the loyal army and security services. The outbreak of the Corona epidemic in Togo in March and the subsequent economic recession may have contributed to limit popular protest against the Gnassingbé regime. The human rights record of the government has improved, but remains poor. Yet, the international community followed a `laissez faire' approach in the interests of regional stability. The economy dropped into recession due to the world-wide economic negative effects of the corona-crisis. The democracy index of the Economic Intelligence Unit, London, still rated Togo as an `authoritarian regime'. – – Umstrittene Verfassungs- und institutionelle Reformen, die im Mai 2019 im Parlament verabschiedet wurden, ermöglichten Präsident Gnassingbé eine vierte und fünfte Amtszeit, da das Gesetz nicht rückwirkend gilt. Im Februar 2020 gewann der Präsident erneut die umstrittenen Präsidentschaftswahlen und festigte damit seine Macht, unterstützt von der loyalen Armee und den Sicherheitsdiensten. Der Ausbruch der Corona-Epidemie in Togo im März und die darauf folgende Wirtschaftsrezession haben möglicherweise dazu beigetragen, die Proteste der Bevölkerung gegen das Gnassingbé-Regime einzudämmen. Die Menschenrechtsbilanz der Regierung hat sich verbessert, ist aber nach wie vor schlecht. Dennoch verfolgte die internationale Gemeinschaft im Interesse der regionalen Stabilität einen ,,Laissez-faire“-Ansatz. Die Wirtschaft geriet aufgrund der weltweiten wirtschaftlichen negativen Auswirkungen der Corona-Krise in eine Rezession. Der Demokratieindex der Economic Intelligence Unit in London stufte Togo weiterhin als ,,autoritäres Regime“ ein.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2020; domestic policy; foreign affairs; socio-economic development; period under review 2020